Serotonin Transporter (5-HTTLPR) Genotype and Childhood Trauma are Associated with Individual Differences in Decision Making - Stoltenberg, Scott F.; Lehmann, Melissa K.; Anderson, Cynthia; Nag, Parthasarathi; Anagnopoulos, Cheryl (Frontiers in Genetics, 2011)
The factors that influence individual differences in decision making are not yet fully characterized, but convergent evidence is accumulating that implicates serotonin (5-HT) system function. Therefore, both genes and environments that influence serotonin function are good candidates for association with risky decision making. In the present study we examined associations between common polymorphisms in the serotonin transporter gene (SLC6A4; 5-HTTLPR and rs25531), the experience of childhood trauma and decision making on the Iowa Gambling Task (IGT) in 391 (64.5% female) healthy Caucasian adults. Homozygosity for the 5-HTTLPR L allele was associated with riskier decision making in the first block of 20 trials (i.e. decision making under ambiguity, p = .004). In addition, mean IGT performance was significantly worse in blocks 3-5 (i.e. decision making under risk, p≤ .05) for those participants who reported experiencing higher levels of childhood trauma. Our findings add to the growing evidence that genetic variation in the 5-HT system is associated with individual differences in decision making under ambiguity; and we report that the experience of childhood trauma is associated with relatively poor decision making under risk.